The impact of noticing activities in increasing vocational students’ grammar skills - Arni Nazira (IRecall Journal, 2025)
This study objective was to discover the impact of noticing activities in learning English grammar. This research employed a quantitative approach with pre-experimental design. The participants of this research were tenth-grade students at Diponegoro Vocational School in Yogyakarta. The data collection of the research was in the form of grammar test including pretest and posttest design for measuring the ability level of participants before and after being given the treatment. Whereas, for data analysis, the researcher used statistical tests such as SPSS to measure the effect of noticing activity. The results unveiled the substantial increase in students' scores from the mean score of pre-test is 43.000, to the post-test score is 87.6471. It means that noticing activities was an effective strategy to enhance students' grammatical skills and recommends the use of its strategy in teaching grammar instruction.